Z-scheme binary 1D ZnWO4 nanorods decorated 2D NiFe2O4 nanoplates as photocatalysts for high efficiency photocatalytic degradation of toxic organic pollutants from wastewater. (15th August 2020) - Reddy, Ch. Venkata; Koutavarapu, Ravindranadh; Reddy, Kakarla Raghava; Shetti, Nagaraj P.; Aminabhavi, Tejraj M.; Shim, Jaesool
Abstract: In this study, dimensionally coupled Z-scheme binary nanocomposites from two-dimensional (2D) NiFe2 O4 nanoplates and one-dimensional (1D) ZnWO4 nanorods are prepared for efficient degradation of an antibiotic tetracycline (TC) and organic dye rhodamine B (RhB) under solar illumination. NiFe2 O4 /ZnWO4 nanocomposites were synthesized by a simple and ecological in-situ hydrothermal method without the use of surfactants. Structural and morphological studies revealed the formation of heterostructure and 1D ZnWO4 nanorods were uniformly distributed over the surface of NiFe2 O4 nanoplates. Light-harvesting capability was improved and optimized by loading with different amounts of ZnWO4 . Photoluminescence analysis demonstrated inhibited nature of the recombination of photo-excited charge carriers in the nanocomposites. Photocatalytic experiments revealed that the nanocomposite exhibited improved Z-scheme electron-transfer for the degradation of TC under solar illumination. In particular, NFZW-20 nanocomposite demonstrated superior photocatalytic degradation of TC of approximately 98% within 105 min. Furthermore, their photocatalytic performance was investigated by RhB dye under the solar irradiation to achieve 98% of degradation of RhB in 70 min. Improved photocatalytic activities are attributed to the Z-scheme electron-transfer mechanism, which could enhance the superior ability of light absorption and reduced recombination rate of the photogenerated charge carriers. Highlights: Z-scheme nanohybrid catalysts from 2D NiFe2 O4 nanoplates and 1D ZnWO4 nanorods are synthesized. Efficient degradation of tetracycline (TC) and rhodamine B (RhB) under solar illumination. Photocatalytic degradation of TC and RhB of 98% within 105 and 70 min respectively. Improved photocatalytic activities are attributed to the Z-scheme electron-transfer mechanism.